The Study of Factors Influencing the Success of Acquisitions in the Case of WPP - Bassil, Ralph (2014)
Literature on mergers and acquisitions often suggest that the majority of transactions fail to deliver anticipated returns, or fail to meet the declared goals. This is studied for a serial acquirer that achieved more than 300 M&As transactions in the period 1985 to 2013. The findings indicate that the acquiring company adopted an acquisitive strategy and achieved phenomenal growth and positive performance. The investigated case provided a better understanding of how to growth can be achieved by relying on acquisitions. The research identified five success factors that were shared among all acquisitions: Clear vision, asset complementarity, relatedness and brand architecture strategy, target size and integration reliance on debt and phenomenal leadership.